Extensive necrotizing fasciitis of the neck: a rare case report - Wan Ali, Wan Nur Amirah Syahirah; Aziz, Azliana; Mohamed Rouse, Muhammad Harith; Abu Kasim, Syuraih Abdullah; Chong, Joan Sue Lynn (Faculty of Medicine, 2025)
Necrotizing fasciitis of the neck and chest wall is a very rare, aggressive infection with high morbidity and mortality. It caused a severe soft tissue infection involving subcutaneous tissue and fascial planes. This infection is more prone in patients with impaired immune systems. Its aggressiveness can also be rapidly fatal, thus requiring aggressive medical and surgical therapy to improve the prognosis. We present a case of a young man with no comorbidities who had an extensive submandibular abscess with necrotizing fasciitis of the neck, anterior chest wall, and descending mediastinitis. Computed tomography of the neck and thorax showed evidence of the initial diagnosis. He was treated with broad-spectrum intravenous antibiotics and surgical debridement of the neck and anterior chest wound. After the surgery, his condition rapidly improved, and he was discharged after a week. The wound was healed after a month of daily dressing.